Multi-objective optimization on the machining parameters for bio-inspired nanocoolant - Keeran, Anamalai; Lingenthiran, Samylingam; K., Kadirgama; Samykano, Mahendran; G., Najafi; D., Ramasamy; M. M., Rahman (Springer, 2019)
The emphasis of this paper is to evaluate the thermophysical properties of crystalline nanocellulose (CNC)-based nanofluid and the optimized machining parameters (cutting speed, feed rate and depth of cut) for machining using CNC-based nanofluid. Cutting tool temperature and formed chip temperature during machining are determined with CNC-based coolant and metal working fluid. Minimum quantity lubrication technique is used to minimize the usage of the coolant. Nanocellulose coolant with a concentration of 0.5% shows better thermal conductivity and viscosity. Total heat produced at the cutting tool and the temperature generated at the chip during machining shows significant improvement using CNCbased nanofluid. Statistical analysis reveals that feed rate and depth of cut contribute around 27.48% and 22.66% toward cutting temperature. Meanwhile, none of the parameters significantly affects the heat transfer. The multi-objective optimization reveals that the optimum parameter for machining using CNC-based nanocoolant is: cutting speed = 120, feed rate = 0.05 and depth of cut = 1.78 which produces heat transfer of 379.44 J and cutting temperature of 104.41 C.